2017
DOI: 10.1186/s12891-017-1631-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise programs among helicopter pilots with transient LBP

Abstract: BackgroundFlight related low back pain (LBP) among helicopter pilots is frequent and may influence flight performance. Prolonged confined sitting during flights seems to weaken lumbar trunk (LT) muscles with associated secondary transient pain. Aim of the study was to investigate if structured training could improve muscular function and thus improve LBP related to flying.Methods39 helicopter pilots (35 men and 4 women), who reported flying related LBP on at least 1 of 3 missions last month, were allocated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
5
13
0
2
Order By: Relevance
“…When considering the pilots as a single group as Brazilian HP, the prevalences of spinal pain (54.8%), low back pain (44.6%), pain during or immediately after flights with less than two hours (36.5%), recurrent (85%), and chronic pain (15%) found in this investigation are similar to the findings in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The LBP prevalence of 44.6% is similar to the 48.1% found by Posh, et al [15].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…When considering the pilots as a single group as Brazilian HP, the prevalences of spinal pain (54.8%), low back pain (44.6%), pain during or immediately after flights with less than two hours (36.5%), recurrent (85%), and chronic pain (15%) found in this investigation are similar to the findings in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The LBP prevalence of 44.6% is similar to the 48.1% found by Posh, et al [15].…”
Section: Discussionsupporting
confidence: 86%
“…More than 98% of pilots that has experienced low back pain have associated it with the flight corroborating previous studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. For the 108 pilots with pain only 2 indicated that the back pain was not related to the flight.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Based on data showing that transient LBP is provoked by awkward sitting and followed by decreased lumbar trunk muscular function, it has been postulated that training of these muscles could reduce the pain [ 6 , 7 ]. In a short-term study, we showed that exercise programs could improve pain, function and quality of health and this was related to a marked improvement of muscular endurance of the lumbar trunk [ 12 ]. In the present study, we have examined the persistence of flying related LBP at mean 26.6 months after intervention.…”
Section: Discussionmentioning
confidence: 99%